A Teaching Practice Study on Applying the CIPP Evaluation Model to Investigate Marine Conservation Lesson Plans and Teaching Aid Practices in Taiwan - Cheng, Wei-Hsin; Wang, Lan-Ting (Advances in Social Sciences Research Journal, 2026)
This study, grounded in teaching practice research, explores the design principles and application value of teaching aids and lesson plans in marine conservation education. Using the CIPP evaluation model as the analytical framework, it summarizes the design characteristics of teaching aids and lesson plans in marine conservation education in recent years and further develops self-made interactive teaching aids for marine conservation education. Through literature analysis, this study collected relevant literature on marine conservation education, ocean literacy education, gamified teaching, and students’ cognitive development, and conducted CIPP analysis on three cases of marine conservation education from the four dimensions of context, input, process, and product to examine their instructional design and implementation effectiveness. The findings show that the design of interactive teaching aids and lesson plans for marine conservation education should emphasize students’ cognitive developmental needs, transform marine conservation knowledge into learning materials that are easier to operate, and incorporate storytelling, gamification, and situational contexts in order to enhance students’ learning motivation, interaction, and participation. This study completed a series of marine conservation teaching aids, including an interactive simulation box, a handheld whale teaching aid, and magnetic interactive devices. Through the design and implementation of these self-made interactive marine conservation teaching aids, as well as multiple revisions of materials, structure, and functions, a tabletop game-based teaching aid with display value, interactivity, educational significance, and operational stability was gradually developed. This study not only responds to the practical needs of marine conservation education in teaching settings, but also, through the processes of teaching aid design, implementation, and reflection, develops interactive instructional materials for teaching practice, which may serve as a basis for future classroom trials and further improvement of teaching aids.